Evaluating an Online Language Assessment Course: Colombian Teachers’ Voices - Giraldo, Frank; García, Lenny (Colombian Applied Linguistics Journal, 2025)
Language assessment literacy (LAL) has emerged as a relatively recent focus in language testing, especially when it comes to fostering this dimension among stakeholders. There are few reports on online assessment courses for English language teachers that discuss their usefulness regarding teachers’ LAL. However, there is a growing call to advance LAL pedagogies and to investigate how assessment courses contribute to teachers’ professional development. In this study, we employed a qualitative research design to ask six Colombian English language teachers to evaluate the contents and activities of an online assessment course specifically designed for them. Data were collected through semi-structured interviews. Our findings indicate that teachers engaged in critical reflection on the course contents, activities, and —considering both what was effective and what was not—by referencing their own assessment practices. Moreover, the findings suggest that course activities, especially quizzes, were instructionally sound, as they promoted a formative assessment approach that, in turn, contributed to development of the teachers’ LAL.